Validation of a Brief CES-D Scale for Measuring Depression and Its Associated Predictors among Adolescents in Chi Linh, Hai Duong, Vietnam - Bui Tu Quyen; Truong Quang Tien; Nguyen Duc Thanh (AIMS Press, 2016)
Objectives: The aims of this paper were to confirm the validity and reliability of a brief CES-D measure for depression and identify the associated factors with the depression among adolescents and youth in Chi Linh, Hai Duong province, Vietnam. Methods: We used data from a prospective-longitudinal study of adolescents and youth (aged 13-17 at baseline) and their parent (N = 1402 mother/father-child dyads). Adolescents' depression was assessed in 2009 and 2013. Parents' connectedness was measured in 2013. Confirmatory factor Analysis (CFA) was used to certify the elementary factors produced by PCA using Comparative Fit Index (CFI), Tucker Lewis Index (TLI) and RMSEA. Multivariate linear regression was used to predict the factors associated with depression. Results: The results demonstrate that the depression items correspond as CFI (0.89), TLI (0.87) and RMSEA (0.084) are acceptable fit indices. The mean score of depression among adolescents and youth was 30.9 (Min = 16 and Max = 70; SD = 8.3). Age (β = -0.01; CI 95% = -0.1; -0.03), parent and youth can talk freely (β = -0.042; CI 95% = -0.08; -0.001) and good health status (β = -0.07; CI 95% = -0.1; -0.03) were found to be significantly associated with depression. Conclusions: Depression scale should be widely applied for screening the depression symptoms of adolescents and youth population. The necessary strategies should be implemented to improve the adolescent and young population's depression status.